Case studies with mathematical modeling of free-radical multi-component bulk/solution polymerizations: Part 2. Issue 6 (3rd June 2017) - Dorschner, David; Jung, Woosung; Riahinezhad, Marzieh; Duever, Thomas A.; Penlidis, Alexander
ABSTRACT: In Part 2 of this series of two extensive overviews of multi-component polymerization case studies, we again present mathematical modeling results with experimental confirmations. Part 2 represents a refinement and expansion of the detailed and extensive mathematical model presented in Part 1 for free-radical, bulk and/or solution multi-component polymerizations. The expansion is mainly with respect to depropagation, thus making the model more fluent at elevated polymerization temperatures and, in parallel, with additional features as backbiting (with systems involving butyl acrylate). The model considers up to six monomers (unique in the literature), for either batch or semi-batch reactor modes. As the simulator database contains several monomers, initiators, solvents, chain transfer agents and inhibitors, all tested over a wide range of polymerization conditions, from data in both academic and industrial laboratories, several hundred combinations of ingredients can be modeled. The many outputs generated by the model include conversion, molecular weight, polymer composition, branching indicators, sequence length, as well as many other polymerization characteristics related to both production rate and polymer quality. Although the only literature data found to date contain a maximum of four monomers, model predictions for homo-, co-, ter- and tetra-polymerizations show reasonable agreement against the data at both regular and elevated temperatures. With these expansions, this model is directed towards becoming a complete free-radical polymerization tool for training and educational uses both in industry and academia.